Optimalisasi Pengelolaan Pertanian Terpadu Guna Mendukung Terwujudnya Desa Mandiri Energi di Desa Sokawera, Kabupaten Banyumas - Sapto Nugroho Hadi; Ida Widiyawati; Furqon Furqon (Institut Pertanian Bogor, 2020)
Most residents in Sokawera Village work as farmers. Population income figures are relatively low, averaging less than IDR 10,000/capita/day. Sokawera village has local potentials that have not been optimally managed, namely independent cattle farms and smallholder coconut plantations. The aim of this activity is to empower the community to optimize the management of eco-friendly integrated agriculture sourced from local potential to support the realization of an energy self-sufficient village. The strategy used in this activity is through the PRA (Participatory Rural Appraisal) approach through the methods of education, training, demonstration plots, and assistance and are equipped with learning techniques while working (learning by doing). This activity began with the implementation of extension activities and transfer of knowledge about the benefits of eco-friendly integrated agriculture, training on the making and utilization of local resources to support the optimization of the management of eco-friendly integrated farming systems such as cattle dung into biogas, biogas waste into liquid and solid organic fertilizers, and coconut shell waste into liquid smoke biopesticides, training in making demonstrations and plots (demonstration plots) of healthy vegetable cultivation, training in processing local agricultural products into value-added products, and training in product marketing strategies through the design and manufacture of attractive product packaging. This activity provides knowledge and skills to the target community regarding the management of local potential such as cow dung waste and coconut shell to optimize environmentally friendly integrated agriculture. This activity is also a starting point for the realization of an energy self-sufficient village. Biogas which is processed from livestock manure is used successfully to replace LPG.